ALEKSIA TANPA AGRAFIA KARENA STROKE INFARK PADA DISTRIBUSI ARTERI SEREBRI POSTERIOR KIRI - *Tjipto Harijono (Neurona Majalah Kedokteran Neuro Sains, 2009)
ALEXIA WITHOUT AGRAPHIA ALSO KNOWN AS OCCIPITAL ALEXIA OR PURE ALEXIA PATIENT RETAIN THE ABILITY TO WRITE BUT ARE UNABLE TO READ EVEN WORDS THAT THEY HAVE JUST WRITTEN AND OVEN HAVE RIGHT HOMONYMOUS HEMIANOPIA A 56 YEAR OLD RIGHT HANDED MAN SUDDENLY HE HAD DIFFICULTY IN READING BUT HE COULD WRITE RIGHT HOMONYMOUS HEMIANOPIA CALOUR NAMING DEFICIT AND CT SCAN SHOWS INFARCT IN TEMPORAL LEFT MEDIAL OCCIPITAL AND SPLENIUM